2021
DOI: 10.1101/gr.275431.121
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced native G-quadruplex stabilization impairs transcription initiation

Abstract: G-quadruplexes (G4s) are noncanonical DNA secondary structures formed through the self-association of guanines, and G4s are distributed widely across the genome. G4 participates in multiple biological processes including gene transcription, and G4-targeted ligands serve as potential therapeutic agents for DNA-targeted therapies. However, genome-wide studies of the exact roles of G4s in transcriptional regulation are still lacking. Here, we establish a sensitive G4-CUT&Tag method for genome-wide profiling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 62 publications
(116 reference statements)
8
91
1
Order By: Relevance
“…Validation with single-stranded nuclease pre-treatment demonstrates that the observed G4 CUT&Tag signals arise from regions where the DNA duplex is melted (Figure 4A ). During revisions of our manuscript, another study also reported development of G4 CUT&Tag in human cells, providing complementary validation for the robustness of the method ( 82 ).…”
Section: Discussionmentioning
confidence: 97%
“…Validation with single-stranded nuclease pre-treatment demonstrates that the observed G4 CUT&Tag signals arise from regions where the DNA duplex is melted (Figure 4A ). During revisions of our manuscript, another study also reported development of G4 CUT&Tag in human cells, providing complementary validation for the robustness of the method ( 82 ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we verified that G4 stabilization could upregulate TNF-α and IL-6, and these cytokines could promote G4 stabilization in cells. We speculate that the folded G4 may regulate the expression of inflammatory genes by the direct interaction with DNA binding proteins such as transcription factors, modulating CpG methylation and shaping chromatin to produce an inflammatory transcriptome ( Lago et al., 2021 ; Li et al., 2021 ; Lyu et al., 2021 ; Tian et al., 2018 ). Therefore, we proposed that the crosstalk of G4 and inflammation may play a vital role in inflammation-derived diseases ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, G4 has been recognized to play an important role in multiple key biological processes that involve replication, transcription, translation, genome instability, and telomere maintenance across multiple species ( Verma et al., 2008 ; Kwok and Merrick, 2017 ; Sengupta et al., 2021 ). In transcription regulation, G4 was found to facilitate the adherence of transcription initiation complex, increase promoter-proximal Pol II pausing, control CpG island methylation and interact with transcription factors ( Lago et al., 2021 ; Li et al., 2021 ; Lyu et al., 2021 ; Mao et al., 2018 ). Huang et al.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was consistent across two different cell lines with distinct G4 landscapes, suggesting that G4 binding is a general property of certain TFs ( 115 ). However, a recent study using the G4-CUT&Tag method demonstrated that ligand-induced G4-stabilization actually reduced transcriptional activity by inhibiting binding of TFs ( 116 ). Thus, while endogenous G4s have been previously associated with enhanced transcription, G4-stabilizing ligands may actually downregulate or suppress transcription ( 116 ).…”
Section: Non-canonical Dna Secondary Structures As Modulators Of Gene Expressionmentioning
confidence: 99%
“…However, a recent study using the G4-CUT&Tag method demonstrated that ligand-induced G4-stabilization actually reduced transcriptional activity by inhibiting binding of TFs ( 116 ). Thus, while endogenous G4s have been previously associated with enhanced transcription, G4-stabilizing ligands may actually downregulate or suppress transcription ( 116 ). Further investigation to see if this pattern is consistent over different ligand concentration, ligands, G4s and genes will be an interesting future direction.…”
Section: Non-canonical Dna Secondary Structures As Modulators Of Gene Expressionmentioning
confidence: 99%